Proximate Analysis of Asian Clam (Corbicula Javanica) - Wungubelen, Kornelius; Batafor, Yosephina M. J.; Larantuka, Karolus. B. (Civiliza Publishing, Indonesia., 2025)
The Asian clam (Corbicula javanica) is a benthic filter-feeding bivalve widely found in Indonesian waters, playing an important role both as a food source and as a bioindicator of aquatic environmental quality due to its ability to accumulate minerals and heavy metals. Despite its ecological and socio-economic importance, scientific data on its nutritional composition in Indonesia remain limited. This study aimed to analyze the proximate composition of C. javanica collected from Gege Waters, Waihali Village, East Flores Regency, to provide baseline information on its nutritional value and ecological relevance. Sampling was conducted purposively in July 2025, and proximate analysis was performed in the laboratory following standardized methods: moisture by gravimetry, ash by incineration, protein by Kjeldahl, fat by Soxhlet extraction, and carbohydrate by difference. The results showed that C. javanica contained high moisture (83.13%), protein (51.27%), ash (12.56%), moderate carbohydrate (28.05%), and low fat (8.13%). These findings confirm its potential as a high-quality protein and mineral source while emphasizing its ecological role as a bioindicator species. In conclusion, this research fills the knowledge gap on the nutritional profile of C. javanica in Indonesian waters, supports its safe utilization for food security, and strengthens its application in sustainable fisheries and environmental monitoring.